Haemophagocytic lymphohistiocytosis: a cause for rare but fatal outcome in tuberculosis. (3rd October 2012) - Aggarwal, Puneet; Kumar, Gunjan; Dev, Nishanth; Kumari, Pushpa
Abstract : Haemophagocytic lymphohistiocytosis (HLH), also called haemophagocytic syndrome (HPS) is characterised by a dysregulated activation and proliferation of macrophages, leading to uncontrolled phagocytosis of platelets, erythrocytes, lymphocytes and their haematopoietic precursors throughout the reticuloendothelial system. Mycobacterium tuberculosis -associated HPS is a rare and underdiagnosed association. We report a 34-year-old male patient diagnosed with tubercular pleural effusion responding poorly to antitubercular treatment. Patient later developed generalised lymphadenopathy, pancytopaenia and liver dysfunction and was eventually diagnosed as HLH. Despite being treated as per HLH protocol 2004 he could not be saved.